Conservation and Documentation of the Tomb Chapel of Menna (TT 69) - Hartwig, Melinda
The Tomb of Menna, Theban Tomb number 69, is located in the Theban necropolis of Sheikh Abd el-Qurna in Luxor, Upper Egypt. The rock-cut tomb is famous for the completeness and superb quality of the paintings that adorn its walls. Structurally, the tomb chapel takes the form of an inverted T, with a forecourt, broad hall, and inner hall leading to a statue shrine. The painted decoration is organized symbolically along a central axis that reflected the deceased’s transition from the land of the living in the east to the land of the dead in the west. As such, the walls in the broad hall are concerned primarily with the official duties and celebrations of Menna’s life, while the walls in the long hall depict scenes of his transition to and life in the hereafter.